P-377 Association between antinuclear antibodies and pregnancy prognosis in recurrent pregnancy loss patients. (6th August 2021) - Yoshihara, H; Sugiura-Ogasawara, M; Kitaori, T; Goto, S
Abstract: Study question: Can antinuclear antibody (ANA) affect the subsequent live birth rate in patients with recurrent pregnancy loss (RPL) who have no antiphospholipid antibodies (aPLs)? Summary answer: ANA did not affect the pregnancy prognosis of RPL women. What is known already: The prevalence of ANA is well-known to be higher in RPL patients. Our previous study found no difference in the live birth rates of ANA-positive and -negative patients who had no aPLs. Higher miscarriage rates were also reported in ANA-positive patients compared to ANA-negative patients with RPL. The RPL guidelines of the ESHRE state that "ANA testing can be considered for explanatory purposes." However, there have been a limited number of studies on this issue and sample sizes have been small, and the impact of ANA on the pregnancy prognosis is unclear. Study design, size, duration: An observational cohort study was conducted at Nagoya City University Hospital between 2006 and 2019. The study included 1, 108 patients with a history of 2 or more pregnancy losses. Participants/materials, setting, methods: 4D-Ultrasound, hysterosalpingography, chromosome analysis for both partners, aPLs and blood tests for ANA and diabetes mellitus were performed before a subsequent pregnancy. ANAs were measured by indirect immunofluorescence. The cutoff dilution used was 1:40. In addition, patients were classified according to the ANA pattern on immunofluorescence staining. Live birth rates were compared between ANA-positive and ANA-negative patients after excluding patients with antiphospholipid syndrome, an abnormal chromosome in either partner and a uterine anomaly. Main results and the role of chance: The 994 patients were analyzed after excluding 40 with a uterine anomaly, 43 with a chromosome abnormality in either partner and 32 with APS. The rate of ANA-positive patients was 39.2 % (390/994) when the 1: 40 dilution result was positive. With a 1:160 dilution, the rate of ANA-positive patients was 3.62 % (36/994). The live birth rate was calculated for 798 patients, excluding 196 patients with unexplained RPL who had been treated with any medication. With the use of the 1: 40 dilution, the subsequent live birth rates were 71.34 % (219/307) for the ANA-positive group and 70.67 % (347/491) for the ANA-negative group (OR, 95%CI; 0.968, 0.707-1.326). After excluding miscarriages with embryonic aneuploidy, chemical pregnancies and ectopic pregnancies, live birth rates were 92.41 % (219/237) for the ANA-positive group and 92.04 % (347/377) for the ANA-negative group (0.951, 0.517-1.747). Using the 1:160 dilution, the subsequent live birth rates were 84.62 % (22/26) for the ANA-positive group, and 70.47 % (544/772) for the ANA-negative group (0.434, 0.148-1.273). Subgroup analyses were performed for each pattern on immunofluorescence staining, but there was no significant difference in the live birth rate between the two groups. Limitations, reasons for caution: The effectiveness of immunotherapies could not be evaluated. However, the results of this study suggest that it is not necessary. Wider implications of the findings: The measurement of ANA might not be necessary for the screening of patients with RPL who have no features of collagen disease. Trial registration number: not applicable